EXTH-52. HARNESSING A B CELL THERAPY TO PROMOTE ANTI-GLIOBLASTOMA HUMORAL RESPONSE. (14th November 2022) - Castro, Brandyn; Fischietti, Mariafausta; Zolp, Andrew; Zhao, Junfei; Hou, David; Nguyen, Linh; Wan, Hanxiao; Zhang, Peng; Han, Yu; Lopez-Rosas, Aurora; Platanias, Leonidas; Stupp, Roger; et al.
Abstract: Glioblastoma (GBM) continues to retain its dismal prognosis despite numerous new therapeutic modalities to target various aspects of the tumor. There is a need to identify new, and even personalized, targetable GBM specific antigens. Our B-cell-based vaccine (BVax) is generated by isolating immune experienced B cells, identified by 4-1BBL, from murine secondary lymphoid organs or patient blood. We have shown this subset of B cells to have anti-tumoral potential in GBM. These cells are strengthened with BAFF, CD40, and IFNg stimulation to form BVax and then activated in vitro to form plasmablasts. Immunoprecipitation-mass spectrometry is performed using BVax -derived antibodies and tumor lysate from the paired patient specimen. We have identified unique antigens bound by BVax -derived antibodies. Given the significant therapeutic benefit we have seen using BVax -derived antibodies in preclinical murine models, we hypothesize that targeting these unique antigens would have significant therapeutic benefit in GBM patients. We focused on antigens that showed a survival benefit with lower expression using CGGA database analysis. We then confirm the presence and prevalence of the antigens within tumor cells in the patient's tissue using immunohistochemistry, identifying some antigens in up to 15% of tumor cells. Using our brain tumor bank repository, we screened other GBM patient's tissue for the presence of these markers to determine the broader applicability of targeting each antigen. We have identified proteins key in extracellular matrix formation which promote tumor growth and progression in cancer, including the ability to induce epithelial-mesenchymal transition. Simultaneously we have developed a computational algorithm to predict which antigens BVax -derived antibodies will bind using single cell RNA sequencing data from GBM patient-derived tumor and BVax, which may have broader applicability to a larger number of patients. Both techniques serve as exciting platforms to identify new therapeutic targets in GBM.